ACTIVISM AND THE CREATION OF SUSTAINABLE MISSION BRANDS: THE PROBLEMATIC CASE OF TURKEY - Kirgiz, Ayca Can (European Scientific Journal, ESJ, 2014)
An evaluation of the concept of activism, which is frequently encountered within the scope of various marketing approaches today and is defined in terms of actions carried out to bring about social or political change, makes it possible to deal with the concept as a part of mission marketing. If a brand takes up a target of change on any subject regarding people, nature, animals or society in the process of creating a marketing and brand strategy as its main approach, this can be deemed to be a mission brand which supports social-environmental activism. Examples of this, however, aren’t commonly encountered and in Turkey there aren’t any brands which have opted to make such a radical move. This study examines the reasons why Turkish brands haven’t taken a mission approach which serves social and environmental activism. The literature section discusses understandings of social marketing which have been engendered by modern notions of marketing and activism, which are one of the most significant social paradigms in today’s world, and provides an analysis of reflections on marketing, mission marketing and the mission brand concept. In light of these issues, the paper examines why Turkish brands haven’t been able to delineate a mission in terms of society and the environment, the most “innocent” branches of activism, and discusses why those issues haven’t been taken up as a constant brand strategy.